Artificial Intelligence: Foresig Artificial Intelligence: prospective in higher technological education: Inteligencia Artificial: Prospectiva en la Enseñanza Técnica Superior. - Torres Morales, Jose Guadalupe; Gibert Delgado, Rosario del Pilar; Becerril Mendoza, Héctor (Acta Universitaria, 2026)
Artificial Intelligence (AI) has emerged as a disruptive technology which can potentially transform higher technological education, especially in engineering teaching. This study aims to analyze its impact on learning by addressing its benefits, challenges, and applications through a comprehensive approach. Using the Delphi methodology -a structured process of consultation with students and teachers through surveys-, key perspectives are gathered and consensus is built on emerging trends. The analysis evaluates AI’s impact across four fundamental dimensions: knowledge, perception, ethics, and the future of education, facilitating the identification of three prospective scenarios for its integration into higher technological education. The proper use of AI could optimize time management, automate processes, and foster spaces for academic and professional development, ultimately contributing to a better quality of life.